Real World Data about the Characteristics of Adult Diabetes Mellitus Patients Visiting Outpatient Department of a Tertiary Care Hospital - Shafat Khatoon, Ghazanfer Ali, Sher Ali, Maria Zafer, Amber Ghaffar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find our characteristics of adult diabetes mellitus (DM) patients visiting outpatient department (OPD) of a tertiary care hospital. Study Design: Observational, cross-sectional study. Place and Duration: Outpatient department of Medicine, Pakistan Institute of Medical Sciences, Islamabad Pakistan from October 2021 to March 2022. Methodology: We included a total of 200 patients. Inclusion criteria were patients of both genders aged 18 to 70 years having type-1 and type-2 diabetes mellitus with a disease duration history of at least 6 months visiting outpatient department. Socio-demographic data along with DM related characteristics including family history of DM, types of DM, types of medications being used and fasting/postprandial blood glucose levels were recorded. Frequency of various DM related complications at the time of enrollment were also noted. Results: In a total of 200 patients of DM, 129 (64.5%) were male and 71 (35.5%) female. Overall, mean age was 45.03±12.46 years while 91 (45.5%) patients were aged between 31 to 45 years. Mean BMI was 23.33±4.75 kg/m2. Positive family history of diabetes was found in 98 (49.0%) patients. Type-1 diabetes mellitus was reported by 13 (6.5%) patients while remaining 187 (93.5%) patients had type-2 diabetes mellitus. Mean Duration of diabetes was 7.65±7.60 years. There were 91 (45.5%) patients who were using oral plus injectable/insulin medications. Overall, mean fasting blood glucose was 148±49.06 mg/dl while mean 2-hour postprandial blood glucose was 235.07±58.80 mg/dl. Neuropathy was the most common diabetes related complications noted in 91 (45.5%) while gastrointestinal related complications were the 2nd most frequent complications observed in 31 (15.5%). Practical Implications: Vast majority of the DM patients reported hyperglycemia during routine follow ups which arises the need to revisit current management strategies. Conclusion: Majority of the patients with DM were male, middle aged and belonged to urban areas of residence. Nearly half of the DM patients reported neuropathy related complications. Keywords: Diabetes mellitus, neuropathy, hyperglycemia, insulin.